Effect of the physiological stabilization process on the corrosion behaviour and surface biocompatibility of AZ91D magnesium alloy - Zhou, Juncen; zhang, Xiaozheng; Li, Qing; Liu, Yan; Chen, Funan; Li, Longqin (Journal of Materials Chemistry B, 2013)
A promising pretreatment method for reducing the electrochemical activity of the magnesium alloy matrix beneath coatings is reported. The physiological stabilization process takes advantage of the localized micro-galvanic corrosion for transforming regions with high activity into a physiological stabilization layer, which can be converted into a protective coating by hydrothermal treatment. Electrochemical and immersion tests revealed that the corrosion resistance of treated AZ91D magnesium alloy was improved. In the cell viability test, the physiological stabilization-hydrothermal samples showed good cell viability for human embryonic kidney (HEK) 293 cells